Pengaruh Self Control dan Penggunaan Gadget Pada Perilaku Prokrastinasi Pada Mahasiswa Tingkat Akhir - Fifin Dwi Purwaningtyas; Starry Kireida Kusnadi; Ressy Mardiyanti; Tutus Risda Sabila; Rosvita Gamul (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2024)
This research aims to try to find out how students can balance the use of gadgets with self-control so that they can minimize the occurrence of procrastination behavior. One of the causes of the problem of procrastination is self-control, students who have activities other than academics predominantly have low self-control. Low self-control can impact academic procrastination, and students consciously use time for other more enjoyable activities, namely by playing with gadgets, and using gadgets without limits, making it difficult for students to control these actions. This research method is non-experimental research because no manipulation of the independent variables was carried out. The variables studied are Problem self-control, use of gadgets, and procrastination. The participants in this research were 202 students (95 men and 107 women) aged 20-26 years, residing in Surabaya; and is currently completing his Thesis (Final Student). The research results show that the level of self-control, level of gadget use, and level of procrastination are moderate, and the F-test analysis hypothesis testing in this research is in the form of a known Sig value. Amounting to 0.021 (<0.05), it can be concluded that self-control and gadget use have a significant effect simultaneously (together) on student procrastination.